A shift in a hake (Merluccius merluccius) population of the NW Mediterranean induced by a combined effect of climate and fishery harvesting - Hidalgo, Manuel; Rouyer, Tristan; Massutí, Enric; Moranta, Joan; Guijarro, Beatriz; Stenseth, Nils Christian (ICES, 2009)
Climate and fisheries are often interacting with each other and producing complex synergic effects on the population dynamics of marine species. The drastic change in the climatic conditions in the North Atlantic (NA) in the early eighties triggered changes in local weather and hydrographical conditions in the Mediterranean Sea. In the other hand, the long term fishery harvesting on the stock of European hake (Merluccius merluccius) off the Balearic Islands (BA, NW Mediterranean) changed the properties of the population and its structure in the early eighties, which could have triggered a different response to the environmental variability. Using time series analysis (on the environmental and hake CPUE time series) and a population simulation model, we examine the hypothesis that these processes are linked and, in turn, a combined effect of fishery harvesting and environmental changes in the NA induced an ecological shift in the hake population off BA. The results points out that the changes in the variance and modes of hake CPUE were consistent with changes in the hydroclimatic variability in the NW Mediterranean induced by the North Atlantic climate. Population simulations show that age-structured populations act like a filter of the environmental fluctuations and can intrinsically generate cycles (‘cohort-resonance effect’) consistent with the 12 yr mode observed in the CPUE before the eighties. Size selective fishing mortality could erode the age structure and change the population filter properties. The population would have changed from internally-generated fluctuations to an externally-forced fluctuations mode after the eighties, increasing its dependency on the recruitment variability. This fits with the observations which show the high dependency of the CPUE on the recruitment variability and the winter condition modes predominating after eighties. Our results emphasize the importance of the interaction between fisheries, environment and internal dynamics that can cause transitory shifts in the behaviour of a population. Keywords: European hake, juvenescent populations, juveniles’ fishery, North Atlantic climate, NW Mediterranean climate, phase transitions, regimen shifts.